Intravenous iron for anaemia in pregnancy: A quantitative study of acceptability and feasibility of its integration into routine antenatal care practice in Nigeria - Opeyemi Rebecca Akinajo; Aduragbemi Banke-Thomas; Kristi Sidney Annerstedt; Lenka Beňová; Yusuf Adetomiwa Adelabu; Nadia Adjoa Sam-Agudu; Bosede Bukola Afolabi (PLoS ONE, 2026)
Background Anaemia in pregnancy (AIP), defined as a haemoglobin concentration of less than 11g/dl, is a significant global health issue, especially in resource-constrained settings. Of all the causes of AIP, iron deficiency anaemia is the commonest, accounting for approximately half of cases. While oral iron treatment is standard according to the WHO recommendation, poor adherence is a concern. Intravenous (IV) iron is an alternative treatment, especially in cases where oral iron is challenging to utilise. However, this intervention is yet to be integrated into routine antenatal care. This study aimed to assess skilled health personnels' (SHPs) perceptions of the acceptability and feasibility of IV iron in managing AIP in Lagos and Kano based on SHP characteristics and changes over time. Methods This was a repeated cross-sectional study embedded within a randomised controlled trial (RCT) conducted in 11 healthcare facilities in Lagos and Kano states, Nigeria. All SHPs trained in implementing IV iron were invited to participate in the study. Data were collected using the Acceptability and Feasibility of Intervention measure (AIM and FIM) survey tools between the RCT baseline in August 2021 and the endline in May 2023. Analysis was done using descriptive statistics, independent and Paired T-tests and Analysis of variance (ANOVA) in Stata. Results Of the 60 SHPs invited at baseline (pre-implementation), 53 (88%) completed the survey. At endline (post-implementation), 39 of the 46 SHPs involved in IV iron implementation responded (85%). When comparing groups, baseline AIM scores differed significantly by state ( p = 0.001), though this was not sustained at endline. No other significant differences were seen by cadre or facility for AIM, and FIM did not differ significantly by state, cadre, or facility at either time point. Among the 20 SHPs who completed both surveys, the AIM score increased from baseline 16.8/20 (Standard deviation, SD = 2.0) to endline (18.5, SD = 2.0) ( p = 0.002). FIM scores also increased over time, 17.1/20 (SD = 2.3) versus 18.2/20 (SD = 1.7) ( p = 0.088). Conclusion Post-implementation, IV iron was perceived as highly acceptable and feasible with no differences across cadre, state, or facility levels. While acceptability significantly improved over time, feasibility also increased, though not statistically significantly at the 0.05 level.